The Effect of Family Size on Education: New Evidence from China's One Child Policy - Laura M. Argys; Susan L. Averett (Institute for the Study of Labor (IZA), 2015)
Social scientists theorize that the inverse relationship between socio-economic status and family size represents a trade-off between the quality and quantity of children. Evaluating this hypothesis empirically requires addressing the simultaneity of the quality and quantity decisions. Researchers have used the unanticipated birth of twins as exogenous variation in family size or the sex composition of the first two children as an instrument for family size with mixed results. We exploit a different source of exogenous variation in family size. The One Child Policy (OCP) in China dramatically reduced Chinese fertility and we examine how the OCP has affected the educational attainment of Chinese migrants to the U.S. Using data from the American Community Survey (2009-2012) and a difference-in-differences strategy our results support the quality-quantity tradeoff theory. We find that education increased more for Chinese migrants born after the OCP than their counterparts from other East Asian countries.
Keywords: I21; J18; 330; education; migration; quality-quantity tradeoff; family size; One Child Policy